RECOMMENDATIONS FOR ACHIEVING MEDIUM- AND HIGH-INTENSITY PHYSICAL / SPORT ACTIVITY IN PHYSICAL EDUCATION TO IMPROVE THE HEALTH AND LEARNING OF CHILDREN AND ADOLESCENTS - Bostjan Šimunič; Tadeja Volmut; Saša Pišot; Matej Plevnik; Urška Čeklić; Nika Pegan; Petra Dolenc; Iztok Retar; Katja Koren (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2016)
The world faces an epidemic of general physical inactivity, impeding the achievement of a sufficient level of medium- and high-intensity physical / sport activities (P / SA). Never in human history were people less physically active than they are now, both at work and in their free time. The most problematic seem to be children and adolescents whose level of P / SA decreases and is not sufficient for maintaining health. School plays an important role in ensuring sufficient and quality P / SA. Physical education is a key period during school when students can be physically active. Consequently, policy makers and moderators of strategies in the field of movement, health and sport should strive to develop the appropriate curriculum and strategies for increasing the volume, intensity and quality of P / SA during physical education. Teachers should pay particular attention, with didactic and methodical approaches, to the achievement of medium- and high-intensity of children's P / SA.